UJI KONSTITUSIONALITAS PASAL 31 AYAT (1) B UU KEJAKSAAN DI MAHKAMAH KONSTITUSI - Sumali, Sumali (Jurnal Bestari, 2008)
This analysis focused on finding the valid and effective formulation about legal standing and the material of judicial review on the Chapter 3I Article (1) b Prosecutor Act on Constitution 1945. This analysis indicated the constitutional failure on the validity variable of legal standing of the applicant for judicial review. Hopefully it could be performed potentially and accurately. At Blitar East Java, the constitutional failure due to the application of aquo chapter occurred. Meanwhile, in term of the aqua chapter. it is found that the application was unconstitutional